Human antibody response to N-glycans present on plant-made influenza virus-like particle (VLP) vaccines - Ward, Brian J.; Landry, Nathalie; Trépanier, Sonia; Mercier, Geneviève; Dargis, Michèle; Couture, Manon; D’Aoust, Marc-André; Vézina, Louis-P. (Vaccine, 2014)
Plant-made biotherapeutics are gathering momentum and some plant glycoproteins are allergens. Glycans with core β1-2xylose and α1,3fucose motifs and antennae terminated by mannose residues (e.g.: MMXF) are found on several plant allergens and can cross-react with glyco-epitopes from other sources. To date, reactivity to these cross-reactive determinants has not been associated with clinical symptoms. We produced VLP vaccines bearing the hemagglutinin(HA) of H5(A/Indonesia/5/05) or H1(A/California/07/09) influenza viruses by transfection of Nicotiana benthamiana. Subjects enrolled in Phase I/II trials were followed for evidence of allergy/hypersensitivity and development of antibodies against plant glyco-epitopes. A total of 280/349 subjects received either one (H1) or 2 doses (H5) of vaccine (5–45μg of HA/dose) intramuscularly including 40 with pre-existing plant allergies. Subjects were monitored for 6 months. IgG and IgE to plant glyco-epitopes were measured by ELISA using corn-/egg-derived avidin and bromelain as target antigens. No subject developed allergic/hypersensitivity symptoms. Some (34%) developed transient IgG and, in some cases IgE, to plant glyco-epitopes but no subject mounted an IgE response to the MMXF motif. Antibodies returned to baseline by 6 months in most subjects. VLP vaccines bearing influenza HA glycoproteins can elicit transient IgG and, in some cases, IgE responses that are not associated with either the development or worsening of allergic/hypersensitivity symptoms.